Rubber growing soils of Northern Mizoram - Their characteristics, and limitations - Satisha G C; Dey S K; Karthikakuttyamma M; Pal T K; Varghese Y A (Journal of the Indian Society of Soil Science, 2002)
Seven representative soil sites of major rubber growing areas in Northern Mizoram were identified and their climatic, soil and site characteristics were studied and assessed for suitability through limitation approach. The suitability criteria for rubber cultivation were developed with special reference to hilly terrain of Mizoram. The prevailing land characteristics of each site were compared with these diagnostic limitations. The steep slopes and low winter temperature of less than 10 oC are the major constraints in the region. Most of the soil-sites studied are moderately suitable except for soils of rolling hills with very high steep slope at 400 and 750 m above mean sea level are marginally suitable for rubber cultivation.
Keywords: Hevea brasiliensis; Limitations; Soil characteristics; Suitability